Screening of in vitro Cytotoxicity, Evaluation of Hepatoprotective and Oxidative Stress Inhibiting Potential of Clitoria ternata in Carbon Tetrachloride Induced Hepatic Damage in Rats - Bhaskara Rao, Dadi; Krishna, G Mohana; Raghava Rao, K V; Kiran, Ch Ravi; Rao, T Raghava (Pharmacognosy Communications)
Background: Clitoria ternata is a herb extensively used in treating a wide variety of ailments. Early researches of C.ternata mainly focused on the evaluation of antitoxic roles of methanolic extract. Objective: The present study focused on evaluating the protective roles of petroleum ether (PE) and chloroform (CE) extracts of C.ternata on CCl4 induced liver damage. Materials and Methods: Hepatoprotective activity was determined by assessing the levels of various hepatic markers like SGOT, SGPT, ALP and total bilirubin content. Inhibition of oxidative stress (antioxidant) analysis was done by estimating the levels of SOD, CAT, TBARS and total protein content. In addition, our study also assesses the anticancer activity against three cell lines namely HeLa, K-562 and MCF-7. Results: CCl4 caused a marked rise in serum marker levels. Both PE and CE of C.ternata decreased the alterations of these effects in the experimental animals and protected the liver tissues against CCl4 induced oxidative stress by increasing the antioxidant defense. Furthermore, both the extracts also exhibited anticancer activity by inhibiting cancer cell proliferation. Conclusion: The results showed that the C.ternata extracts possess cytotoxic, antioxidant, hepatoprotective roles and supports their use in traditional medicine.
Keywords: Liver; Clitoria ternata; CCl4; cytotoxic activity; lipid peroxidation; antioxidants